Thermal And Metallographic Parameters Evolution During Solidification Of Zn-Sn Alloys - Desrosin, Wilky (2014)
In the present research the horizontal directional solidification Zn-Sn alloys (Zn-4wt.%Sn, Zn-6wt.%Sn, Zn-10wt.%Sn and Zn-30wt.%Sn) was carried out by extracting heat in two opposite directions. For this purpose, ceramic molds, a muffle, a horizontal furnace with two heat extraction systems at the ends, a measurement, acquisition and recording temperature system, eight K-type thermocouples and an electronic recorder were used. The main parameters involved in the columnar-to-equiaxed transition, CET, were: the moment of start and end of solidification at each position under consideration, cooling rates, the average temperature gradients and critical temperature gradients at the CET, the average speed of liquid and solid interphases left and right, advancing in opposite directions. Also, solidification kinetics was found to be different between horizontal solidification two-way heat extractions, with preliminary results of the vertical unidirectional solidification. In the solidification experiments, the velocity and accelerations of the liquidus and solidus interphases usually occurs at the end solidification zone of the samples.